The Growth of Pathogens and Beer Spoilage Organisms in No and Low Alcohol Beers and Strategies to Prevent Their Growth - Bartlett, Connor (2023)
There has been an increase in demand for no and low alcohol alternatives to beer, including their serving on-trade through draught dispense systems. Ethanol aids in regular beers microbiological stability, reducing this could lead to product spoilage. Additionally, the methods used to produce no and low alcohol beers can significantly affect other beer parameters, which may be important for susceptibility to microbial growth. This new environmental niche of no and low alcohol beers has already been shown to be more susceptible to microbial spoilage and pathogenic growth than their full alcohol counterparts. This study assessed the growth of Pichia membranifaciens, Levilactobacillus brevis, Rahnella spp., Escherichia coli 0157:H7 and Salmonella Typhimurium in three low alcohol beers and one full alcohol counterpart. Along with the antimicrobial effects of commonly used food and beverage preservatives, sodium benzoate, potassium sorbate and sulphur dioxide were studied on these microorganisms. Using an Omnilog® the effects of pH, varying doses and combinations of preservatives was tested on the growth of P. membranifaciens and L. brevis on one of the low alcohol beers. The differences in spoilage and pathogen growth between the beers was discussed in relation to the pH, sugar composition, elemental composition, and production method. The growth of P. membranifaciens was greater in every low alcohol beer tested compared to the full alcohol beer in spoilage and Omnilog® trials. This appeared to be caused by the reduction in ethanol content. The growth of L. brevis was highest in Brand 1 0.5% this appeared to be related to the higher glucose content. Rahnella spp. Only grew in Brand 1 0.5% and Brand 2 0.5%. E. coli 0157:H7 (Non-STEC) didn’t grow in any of the beers tested. S. Typhimurium was only able to grow slowly in Brand 2 0.5%. It was observed to grow rapidly in a modified Brand 1 0.5% but was inhibited by all the preservatives tested. Sodium benzoate and potassium sorbate were effective at reducing the growth of all the spoilage organisms, with P. membranifaciens and L. brevis being reduced to growth levels comparable with a full-alcohol beer. Sulphur dioxide was able to completely inhibit growth of Rahnella spp. in Brand 1 0.5%. The differences in growth of spoilers and pathogens appears to be related to the combination of pH, ABV, glucose, fructose, and maltose content of the beer. There were no synergistic effects observed when using combinations of the preservatives. Reducing the pH to 3.8 or raising it to 4.45 did not appear to influence the effectiveness of any of the preservatives tested against P. membranifaciens or L. brevis. The use of preservatives should be considered when producing NABLABs destined to be served on draught dispense to reduce their susceptibility to spoilage and prevent the growth of S. Typhimurium.